Liver resections for metastasis - Camaño, Mario; Rubio, Fulvio; Palumbo, Jorge; Parcerisa, Raúl (Cirugía del Uruguay, 1992)
The author presents a seies of 19 hepatic resections due to seconday liver tumors caried out in general surgey sevices of three sma1 and mediu